THE DEVELOPMENT OF EMPIRIC-ANALYTICAL FORMULA FOR WATER EVAPORATION (CONDENSATION) FROM BRINE OF THE EASTERN REMEDIAL BASIN OF SAKY LAKE - Sitnikov, A.B. (Institute of Geological Sciences, NAS of Ukraine, 2016)
The features for the conditions of aqueous solutions at the high mineralization, in particular, marine and lake brine in the sort of Saky Lake are summarized. The theoretical conclusion is present for the calculating formula of water evaporation from the basin of remedial brine formed by the refill of seawater and physical evaporation obtained from the meteorological data. The complicated character of moisture movement in the subsurface layer can be taken into account by the so called empirical constant, which is estimated by the methods of balance among salts and water.